Generic Bifurcations of Planar Filippov Systems via Geometric Singular Perturbations - de Carvalho, Tiago [UNESP]; Tonon, Durval Jose (Belgian Mathematical Soc Triomphe, 2011)
In this paper we deal with non-smooth vector fields on the plane. We prove that the analysis of their local behavior around certain typical singularities can be treated via singular perturbation theory. In fact, after a regularization of a such system and a blow-up we are able to bring out some results that bridge the space between non-smooth dynamical systems presenting typical singularities and singularly perturbed smooth systems.
Keywords: geometric singular perturbation; non-smooth vector fields; bifurcation; fold-fold singularity